Modeling of PV systems by using Matlab/Simulink - Jaycelyne, Lemba Jerry (2012)
Solar energy is one of the many forms of renewable energy on earth. By using photovoltaic cell which converts sunlight directly into electricity, this energy can be harnessed. This form of energy has been accepted worldwide as high potential energy alternative energy as current research and markets have shown that solar photovoltaic (PV) is amongst the fastest growing and most promising forms of renewable energy for electricity generation. A photovoltaic array (PVA) simulation model to be used in MATLAB/SIMUL1NK is developed based on the specification data provided in the manufacturer's data sheets. The model is developed using basic circuit equations of the photovoltaic (PV) solar cells including the effects of solar irradiation and temperature changes. In the present modeling, the focus is only on the cell, module, and array. The model for the proposed range of irradiance and temperature as model inputs, with the corresponding values of voltages, currents, and power as outputs is presented. The objective of this project is to simulate the output current and power characteristics and observe the effects of solar irradiance and temperature changes of the PV system. This project is also to determine and analyze the maximum power point tracker (MPPT) of the PV model. Results from simulation will be compared with points taken directly from the manufacturer's published curves. Overall findings will indicate that the modeling using MATLAB/SIMULINK can be further used for investigation and make improvement in order to identify which best technologies to be implemented.